Linear polymeric ionic liquids as phase-transporters for both cationic and anionic dyes with synergic effects1. Issue 39 (21st October 2015) - Zhao, Hualei; Yu, Yanting; Li, Zonghao; Luo, Bin; Wang, Xinhang; Wang, Yanping; Xia, Yumin
<x xml:space="preserve">Abstract</x> Linear polymeric ionic liquids were synthesized and demonstrated to be very effective transporters for both anionic dye methyl orange (MO) and cationic dye methylene blue (MB) from water to chloroform individually as well as simultaneously.